Characterisation and prognostic impact of immunoparesis in relapsed multiple myeloma. (28th February 2020) - Chakraborty, Rajshekhar; Rybicki, Lisa; Nakashima, Megan O.; Dean, Robert M.; Faiman, Beth M.; Samaras, Christy J.; Rosko, Nathaniel; Dysert, Hayley; Valent, Jason; Anwer, Faiz
Summary: Characterisation and prognostic impact of immunoparesis in relapsed multiple myeloma (MM) is lacking in the current literature. We evaluated 258 patients with relapsed MM, diagnosed from 2008 to 2015, to investigate the prognostic impact of deep immunoparesis on post‐relapse survival. On qualitative immunoparesis assessment, no, partial and full immunoparesis was present in 9%, 30% and 61% of patients, respectively. Quantitative immunoparesis was assessed by computing the average relative difference (ARD) between polyclonal immunoglobulin(s) and corresponding lower normal limit(s), with greater negative values indicating deeper immunoparesis. The median ARD was −39%, with an optimal cut‐off of −50% for overall survival (OS) by recursive partitioning analysis. Deep immunoparesis (ARD ≤–50%) was associated with a higher tumour burden at first relapse compared to none/shallow [ARD >−50%] immunoparesis. The OS ( P  = 0·007) and progression‐free survival (PFS; P  < 0·001) differed significantly between the deep and none/shallow immunoparesis groups. Kaplan–Meier estimates for 3‐year OS were 36% and 46%, and for 2‐year PFS were 17% and 27%, respectively. On multivariable analysis (MVA) for PFS, both qualitative and quantitative immunoparesis retained negative prognostic impact independently. However, only quantitative immunoparesis was independently prognostic for OS on MVA. Depth of immunoparesis in relapsed MM is an important prognostic factor for post‐relapse survival in the era of novel agents and continuous therapy.